2018
DOI: 10.1038/s41388-018-0244-x
|View full text |Cite
|
Sign up to set email alerts
|

WNT ligands control initiation and progression of human papillomavirus-driven squamous cell carcinoma

Abstract: Human papillomavirus (HPV)-driven cutaneous squamous cell carcinoma (cSCC) is the most common cancer in immunosuppressed patients. Despite indications suggesting that HPV promotes genomic instability during cSCC development, the molecular pathways underpinning HPV-driven cSCC development remain unknown. We compared the transcriptome of HPV-driven mouse cSCC with normal skin and observed higher amounts of transcripts for Porcupine and WNT ligands in cSCC, suggesting a role for WNT signaling in cSCC progression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 41 publications
(63 reference statements)
0
25
0
Order By: Relevance
“…Recently, it has been found that LGK974, which is an inhibitor of the enzymatic activity of Porcupine, significantly reduced β-catenindependent Axin2 expression in approximately one third of 96 head and neck cancer cell lines analyzed [24]. Moreover, this compound was found to reduce Wnt/β-catenin pathway activation in papillomavirus-driven cutaneous squamous cell carcinomas [35]. IWP-2, another Porcupine inhibitor which has a chemical structure different from LGK974, was tested in our study.…”
Section: Discussionmentioning
confidence: 88%
“…Recently, it has been found that LGK974, which is an inhibitor of the enzymatic activity of Porcupine, significantly reduced β-catenindependent Axin2 expression in approximately one third of 96 head and neck cancer cell lines analyzed [24]. Moreover, this compound was found to reduce Wnt/β-catenin pathway activation in papillomavirus-driven cutaneous squamous cell carcinomas [35]. IWP-2, another Porcupine inhibitor which has a chemical structure different from LGK974, was tested in our study.…”
Section: Discussionmentioning
confidence: 88%
“…This study speci ed that miR-214 could negatively target VEGFA and Bcl-2 and the subsequent activation of the Wnt/βcatenin pathway in CSCC cells. The signi cance of the Wnt/β-catenin signaling in CSCC initiation and progression has been underscored [24], and knockdown of β-catenin led to a marked decline in the colony-forming activity of SCC12 cells [25]. circ_CHFR knockdown was observed to impede the β-catenin expression via promoting miR-214-3p [26].…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of Porcupine by C59 blocked the secretion of WNT-3A by dysplastic oral keratinocytes and reduced nuclear β-catenin level, leading to the inhibition of target gene (CCND1, BIRC5) expression [35]. Moreover, Porcupine inhibitors (LGK974 and C59) impaired the initiation and growth of HPV-driven cutaneous SCC and reduced the expression of CSC markers [126].…”
Section: Functional Significance Of Wnt/β-catenin Pathway Dysregulationmentioning
confidence: 99%
“…reduced stemness [102] decreased cell invasion [106] cell cycle arrest, reduced cell migration, induction of apoptosis [51,107] decreased cisplatin resistance [102] increased radiosensitivity [135] Porcupine IWP-2 inhibitor inhibition of UCA1dependent Wnt activation reduced cell proliferation and migration [84] LGK974 inhibitor reduced Wnt target gene expression reduced tumor growth [125] C59 inhibitor reduced secretion of WNT-3A, reduced CCND1 and BIRC5 expression impaired HPV-driven transformation [126] CBP ICG-001 inhibitor altered gene expression cell cycle arrest, induction of apoptosis, reduced stemness, tumor growth and metastasis [130,131] PI3K pathway emodin inhibition of PI3K/Akt/ β-catenin pathway reduced cell invasiveness [111] pyrithione zinc reduced expression of CCND1 and c-MYC reduced cell proliferation and invasion, apoptosis [119] CUL4B knockdown reduced expression of CCND1, c-MYC, MMP-7 reduced cell growth, migration and invasion [113] Funding: This work was funded by the Polish National Science Centre, grant number 2014/13/D/NZ7/00300.…”
Section: Lef1mentioning
confidence: 99%